2009
DOI: 10.5004/dwt.2009.847
|View full text |Cite
|
Sign up to set email alerts
|

Resident's strategy survey on a new end use of recycled water in Australia

Abstract: The concept of using recycled water for washing machine was introduced as a new end use. As there is a noticeable lack social research in understanding the general public perceptions of this application, the resident's strategy survey was carried out at some selective suburbs in Sydney with demographically based significant differences of general, gender, age, education, and property style and ownership.The survey indicates that the majority in the community considers the use of recycled water for washing mach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 1 publication
0
11
0
Order By: Relevance
“…Secondly, to embody varying degrees of concern on different evaluation criteria in decision making, weighting process becomes essential in MCA which is to assign higher weights to more important criteria and smaller weights to less important criteria. Although recent works have given more attention to recycled water quality and operational and maintenance cost (Ngo et al, 2009), or highlighted the importance of environmental performances (Chen et al, 2013b), the case-specific context can facilitate the need for differential weighting. Yet in some cases, due to lack of sufficient expertise, decision makers might be less confident in assigning specific weight to each criterion, making the weight values be highly variable.…”
Section: Multi-criteria Analysis (Mca) In Decision Makingmentioning
confidence: 99%
“…Secondly, to embody varying degrees of concern on different evaluation criteria in decision making, weighting process becomes essential in MCA which is to assign higher weights to more important criteria and smaller weights to less important criteria. Although recent works have given more attention to recycled water quality and operational and maintenance cost (Ngo et al, 2009), or highlighted the importance of environmental performances (Chen et al, 2013b), the case-specific context can facilitate the need for differential weighting. Yet in some cases, due to lack of sufficient expertise, decision makers might be less confident in assigning specific weight to each criterion, making the weight values be highly variable.…”
Section: Multi-criteria Analysis (Mca) In Decision Makingmentioning
confidence: 99%
“…Dolnicar and Saunders [7], reviewed eight American studies and found that the average willingness on use of recycled water was 80%. In a survey on public attitudes towards recycled water, Ngo et al [8], found public health, water clearness, cost and machine durability as major concerns of public. Pham et al [9], performed similar surveys in Sydney and revealed that only 60% of the respondents supported the use of recycled water in washing machine.…”
Section: Introductionmentioning
confidence: 99%
“…According to statistics on typical water usage in Sydney metropolitan households, laundry use consumes up to 20% of total water demand [11][12][13]. A significant reduction in household drinking water demand could therefore be achieved if the drinking quality water for clothes washing was replaced with recycled water.…”
Section: Introductionmentioning
confidence: 99%
“…However, the laundry use of recycled water has not been sufficiently investigated and thus until today there is no sufficient evidence and supporting quality guidelines for this particular use [10,12]. Moreover, the effects of various heavy metals present in recycled water on quality of clothes and washing machines have not been reported [11].…”
Section: Introductionmentioning
confidence: 99%